When the Questions Breaks the Mold (2015)
Researchers and children have gathered for ten years to develop science communication workshops. It is an experience that also transforms the eyes of experts. Findings reflected in this year's presentation at the Congress of the Network for the Popularization of Science and Technology, RedPop